Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Penerapan Bangun Ruang Kelas Ix Smp Negeri 2 Cepogo - Jumiyati, Jumiyati; , Masduki, S.Si, M.Si; , Sri Rejeki, M.Pd, M.Sc (2016)
The purpose of this study are to find out the errors of students and the factors that cause errors in solving problem of geometrical implementation in class IX SMP Negeri 2 Cepogo. Type of this research is descriptive quantitative study. The subject of this research are students of class IX who make mistakes in solving problem of geometrical implementation. Methods of data collection using observation, testing, and documentation. Data analysis technique performed interactively. The results showed the mistakes made by the students is the error associated with drawing geometry, errors related logic, errors in calculating. Factors that cause the students' errors in solving problem of geometrical implementation in class IX SMP Negeri 2 Cepogo are students drawing are not seriously, students forget or do not know the formula to be used, students can not understand the intent of the matter, students are not careful in doing, and students enter the wrong numbers into the formula.